ChemInform Abstract: Cascade Michael—Intramolecular Transesterification—Elimination Reaction of 3, 4‐Dihydro‐3‐nitrochromen‐2‐ones and β, γ‐Unsaturated α‐Oxo Esters: An Efficient Access to 2‐Pyrone Derivatives. Issue 6 (23rd January 2015) - Zhang, Li; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract A new and efficient method for the preparation of 2‐oxopyrone‐6‐carboxylates under mild conditions is described.